Strategi Pembelajaran Satu Mahasiswa Satu Karya terhadap Keterampilan Menulis Mahasiswa - Laeli Zzakiyah; Zaenal Arifin (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
This article discusses the one-student, one-work learning strategy for the writing skills of INISNU Temanggung students. This study aimed to determine the Sama Saya learning strategy on students' writing skills. This study uses a type of qualitative research, namely descriptive analysis. The data collection carried out in this study used direct interview techniques, observation, and documentation. This study states that the learning strategy of one student is to work through habituation, culture, and program integration in the academic curriculum. The findings of this study follow the concept and theory of structural functionalism of Talcott Persons, commonly known as the AGIL scheme (Adaptation, Goal attainment, Integration, Latent-pattern-maintenance), so this strategy is fundamental and practical to improve students' writing skills.